INTERNATIONAL CONFERENCE „FROM BENCH TO BED: CHALLENGES IN CANCER CARE“ SCHEDULE - chirurgija, Lietuvos (Lietuvos chirurgija, 2013)
DEDICATED TO 80TH ANNIVERSARY OF LITHUANIAN SOCIETY OF ONCOLOGYSEPTEMBER 20-21, 2013DRUSKININKAI